2015
DOI: 10.1371/journal.pgen.1005399
|View full text |Cite
|
Sign up to set email alerts
|

EIN3 and ORE1 Accelerate Degreening during Ethylene-Mediated Leaf Senescence by Directly Activating Chlorophyll Catabolic Genes in Arabidopsis

Abstract: Degreening, caused by chlorophyll degradation, is the most obvious symptom of senescing leaves. Chlorophyll degradation can be triggered by endogenous and environmental cues, and ethylene is one of the major inducers. ETHYLENE INSENSITIVE3 (EIN3) is a key transcription factor in the ethylene signaling pathway. It was previously reported that EIN3, miR164, and a NAC (NAM, ATAF, and CUC) transcription factor ORE1/NAC2 constitute a regulatory network mediating leaf senescence. However, how this network regulates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
243
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 286 publications
(275 citation statements)
references
References 49 publications
(74 reference statements)
6
243
1
1
Order By: Relevance
“…Many previous studies have identified the TFs responsible for controlling Chl metabolism in leaves (Lim, 2003; Lin et al, 2015; Wen et al, 2015). Three TFs, ANAC046, ETHYLENE INSENSITIVE3, and ORE1, positively regulate Chl degradation by binding to the promoter regions of NYC, SGR1 , and PaO (Qiu et al, 2015; Oda-Yamamizo et al, 2016). FLU, a negative regulator of Chl biosynthesis in A. thaliana , may mediate its regulatory effect through interaction with enzymes (GSA and CHlH) involved in Chl biosynthesis (Meskauskiene et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Many previous studies have identified the TFs responsible for controlling Chl metabolism in leaves (Lim, 2003; Lin et al, 2015; Wen et al, 2015). Three TFs, ANAC046, ETHYLENE INSENSITIVE3, and ORE1, positively regulate Chl degradation by binding to the promoter regions of NYC, SGR1 , and PaO (Qiu et al, 2015; Oda-Yamamizo et al, 2016). FLU, a negative regulator of Chl biosynthesis in A. thaliana , may mediate its regulatory effect through interaction with enzymes (GSA and CHlH) involved in Chl biosynthesis (Meskauskiene et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…b,d), and, further, PIFs, ORE1, EIN3 and/or ABI5 together regulating chlorophyll catabolism genes (Fig. e) (Sakuraba et al ., ; Song et al ., ; Qiu et al ., ).…”
Section: Coherent Feed‐forward Regulationmentioning
confidence: 97%
“…Combining molecular genetic analysis with systems biology approaches has also revealed complex gene regulatory networks governing leaf senescence, such as a trifurcate feedforward loop including ETHYLENE-INSENSITIVE 2, miR164, and ORESARA1/ANAC092 ). EIN3 and additional NAC transcription factors (TFs) were further found to be involved in the leaf senescence network (Balazadeh et al, 2011;Hickman et al, 2013;Li et al, 2013;Kim et al, 2014a;Qiu et al, 2015). On the other hand, comprehensive profiling of molecular programs has been revealed by time-course transcriptome analysis during early and late leaf development (Beemster et al, 2005;Efroni et al, 2008;Breeze et al, 2011;Andriankaja et al, 2012;Thatcher et al, 2015).…”
mentioning
confidence: 99%